CYFIP1 coordinate with RNMT to induce osteosarcoma cuproptosis via AURKAIP1 m7G modification - Zili Lin; Ziyi Wu; Yizhe He; Xiangyao Li; Wei Luo (Molecular Medicine)
Abstract Osteosarcoma (OS) presents challenges due to its genomic instability and complexity, necessitating investigation into its oncogenesis and progression mechanisms. Recent studies have implicated m7G, a post-transcriptional modification, in the development of various cancers. However, research on m7G modification in OS remains limited. This study aimed to explore the impact of m7G modification in OS, focusing on the role and mechanism of CYFIP1, a member of m7G cap binding complexes. Our findings demonstrated prominent anti-OS effects of CYFIP1 in vitro and vivo. Mechanistically, CYFIP1 collaborated with RNMT to induce the m7G methylation of AURKAIP1 mRNA, which resulted in the stability and the increasing translation of AURKAIP1 mRNA. AURKAIP1, a kind of mitochondrial small ribosomal subunit protein, exhibited increased expression, leading to the dysregulation of mitochondrial translation. This, in turn, caused an increase in the expression of FDX1, eventually triggering cuproptosis in OS cells and repressing OS occurrence and progression. In summary, our study identified the CYFIP1/RNMT/AURKAIP1/FDX1 axis as a potential therapeutic target for OS. These insights contribute to OS research and may guide the development of novel treatments for this challenging disease.